Effects of renal sympathetic denervation on the course of congestive heart failure combined with chronic kidney disease: Insight from studies with fawn-hooded hypertensive rats with volume overload induced using aorto-caval fistula - Honetschlagerová, Zuzana; Škaroupková, Petra; Kikerlová, Soňa; Husková, Zuzana; Maxová, Hana; Melenovský, Vojtěch; Kompanowska-Jezierska, Elżbieta; Sadowski, Janusz; Gawrys, Olga; Kujal, Petr; Červenka, Luděk; Čertíková Chábová, Věra (Clinical and experimental hypertension, 2021)
Background: The coincidence of congestive heart failure (CHF) and chronic kidney disease (CKD) results in poor survival rate. The aim of the study was to examine if renal denervation (RDN) would improve the survival rate in CHF induced by creation of aorto-caval fistula (ACF).Methods: Fawn-hooded hypertensive rats (FHH), a genetic model of spontaneous hypertension associated with CKD development, were used. Fawn-hooded low-pressure rats (FHL), without CKD, served as controls. RDN was performed 4 weeks after creation of ACF and the follow-up period was 10 weeks.Results: We found that intact (non-denervated) ACF FHH exhibited survival rate of 58.8% (20 out of 34 rats), significantly lower than in intact ACF FHL (81.3%, 26/32 rats). In intact ACF FHL albuminuria remained stable throughout the study, whereas in ACF FHH it increased significantly, up to a level 40-fold higher than the basal values. ACF FHL did not show increases in renal glomerular and tubulointerstitial injury as compared with FHL, while ACF FHH exhibited marked increases in kidney injury as compared with FHH. RDN did not improve the survival rate in either ACF FHL or ACF FHH and did not alter the course of albuminuria in ACF FHL. RDN attenuated the albuminuria, but did not reduce the kidney injury in ACF FHH.Conclusions: Our present results support the notion that even modest CKD increases CHF-related mortality. RDN did not attenuate CHF-dependent mortality in ACF FHH, it delayed the progressive rise in albuminuria, but it did not reduce the degree of kidney injury.
Keywords: Heart Failure; krysa rodu Rattus; Animals; Kidney; Renal Insufficiency, Chronic; hypertenze; srdeční selhání; Sympathectomy; píštěle; zvířata; sympatektomie; Hypertension; ledviny; Fistula; Rats; chronická renální insuficience